Antibiotic Resistant and Plasmid Conjugative Study of Salmonella typhi - Haji Saeed Akreyi, Waleed; Younis Yousif, Samira; Assafi, Mahde (Jurnal Teknologi Laboratorium, 2018)
The emergence of multi-drug resistant (MDR) bacteria has endangered the efficacy of antibiotics treatment of pathogenic bacteria worldwide. The aim of this research was to investigate the incidence of Salmonella enterica serovar Typhi in Duhok city, Iraq. Specimens of blood and stool were recruited from 267 patients. S. Typhi isolates were diagnosed depending on morphology, biochemical and serological tests. S. Typhi isolates were tested for their antibiotic resistance. Multi-drug resistant S. Typhi isolates were conjugated with E. coli HB101. The plasmid profile of transconjugants was investigated. 15/267 (5.6%) S. Typhi isolates were identified. Based on their biochemical tests, S. Typhi isolates were categorized into two biotypes (I, 26.66% and II, 73.33%). Four resistance patterns were observed. The resistant pattern to ampicillin and tetracycline was the higher (46.6%). Conjugation experiment showed that all antibiotic markers were transferred from S. Typhi to E. coli HB101 with a conjugation frequency of (0.38Ã—10-5). 13.3% of the S. Typhi isolates were multi-drug-resistant resistant and had two small plasmids. Transconjugants E. coli acquired the resistance from the multi-drug resistant S. Typhi. Antibiotics treatment of the pathogens could be hindered by the constant rise of multi-drug-resistant. Further studies are needed to study the mobile genetic elements and their contribution to antibiotics resistance.